11CO bonds made easily for positron emission tomography radiopharmaceuticals. (8th June 2016) - Rotstein, Benjamin H.; Liang, Steven H.; Placzek, Michael S.; Hooker, Jacob M.; Gee, Antony D.; Dollé, Frédéric; Wilson, Alan A.; Vasdev, Neil
Abstract : This review explores 11 C-carbonylation as an alternative set of strategies to 11 C-methylation for the design and development of radiotracers for positron emission tomography. Abstract : The positron-emitting radionuclide carbon-11 ( 11 C, t 1/2 = 20.3 min) possesses the unique potential for radiolabeling of any biological, naturally occurring, or synthetic organic molecule for in vivo positron emission tomography (PET) imaging. Carbon-11 is most often incorporated into small molecules by methylation of alcohol, thiol, amine or carboxylic acid precursors using [ 11 C]methyl iodide or [ 11 C]methyl triflate (generated from [ 11 C]carbon dioxide or [ 11 C]methane). Consequently, small molecules that lack an easily substituted 11 C-methyl group are often considered to have non-obvious strategies for radiolabeling and require a more customized approach. [ 11 C]Carbon dioxide itself, [ 11 C]carbon monoxide, [ 11 C]cyanide, and [ 11 C]phosgene represent alternative reactants to enable 11 C-carbonylation. Methodologies developed for preparation of 11 C-carbonyl groups have had a tremendous impact on the development of novel PET tracers and provided key tools for clinical research. 11 C-Carbonyl radiopharmaceuticals based on labeled carboxylic acids, amides, carbamates and ureas now account for a substantial number of important imaging agents that have seen translation to higher species and clinical research of previously inaccessible targets, which is a testament to the creativity, utility and practicality of the underlying radiochemistry.